Federal Democracy Nepal: An Assessment of Two Years Democratic Practices - Chetri, Than Bahadur (Journal of Political Science, 2020)
Nepal is on the way of institutionalizing federal political system. New democracy faces a number of challenges in institutionalizing. This paper, aims to understand the state of democratic practices and prospects of democracy in Nepal. It adopts political system approach and takes political ideas, power sharing, resource distribution, social identities, political values as independent variables and stability of democracy as dependent variable. It argues the prospect of democracy is uncertain. Country lacks several preconditions which are necessary for the success of federal democracy. Federalism is difficult to flourish in poor economy based society, incompatible political values, weak institution and poor governance.